Functionalization of carbon nanotubes for high-performance polymer composites - Yuan, Wei (2012)
Carbon nanotubes (CNTs) are promising nanofillers for light weight and high strength polymer composites due to their large aspect ratio, low density, and exceptional mechanical properties. Two major obstacles to the application of CNTs in polymer composites are their tendency to form bundles and aggregates, and low interfacial adhesion with polymer matrix. To solve these problems, both covalent and noncovalent strategies have been developed for functionalization of CNTs. This thesis centers on the design and synthesis of a series of polyimide dispersants to functionalize CNTs via either noncovalent approach or combination of covalent and noncovalent approaches, for fabrication of high-performance cyanate ester (CE) and polyimide (PI) composites. These dispersants effectively disperse CNTs via π−π interaction with nanotube sidewalls, and strongly interact with both CNTs and matrix to improve the nanotube/matrix interfacial adhesion, leading to significantly enhanced mechanical properties of composites. Noncovalent functionalization of CNTs is an attractive option for compatibilization of nanotubes with the matrix as it effectively disperses CNTs and preserves the graphene structure of nanotubes. A novel comb-like polymer, polyimide-graft-bisphenol A diglyceryl acrylate (PI-BDA), was first synthesized and shown to be highly effective in dispersing and debundling single-walled carbon nanotubes (SWNTs). SWNTs dispersed with PI-BDA were added into CE (epoxy-modified) matrix and composite fibers were successfully fabricated by reactive spinning. PI-BDA dispersant interacts noncovalently with SWNTs to produce minimal damage to the SWNTs but covalently reacts with CE matrix, resulting in high mechanical reinforcement. Only 1 wt% of PI-BDA functionalized SWNTs increased the tensile modulus and strength of composite by 80% and 70% over that of neat resin, which are higher than the results of other CNT/thermosetting composites. We further investigated the effect of the side-chain structure of rigid polyimide dispersant on the dispersion of SWNTs and mechanical properties of SWNT/CE composites. Three kinds of polymer, including polyimide without side-chain (PI), polyimide-graft-glyceryl 4-nonylphenyl ether (PI-GNE) and PIBDA, were synthesized and used to disperse SWNTs and improve the mechanical properties of CE. PI-BDA and PI-GNE are equally highly effective at dispersing SWNTs in dimethylformamide (DMF), whereas PI is less effective. PI-BDA functionalized SWNTs were found to be the most effective fillers for reinforcing CE due to the unique side-chain of PI-BDA, which is more compatible with CE matrix and leads to better SWNT dispersion and stronger SWNT/CE interfacial bonding. Though noncovalent functionalization can disperse high concentration of CNTs without damaging nanotube structure, the interaction between CNTs and dispersant is relatively weak. Therefore, we developed a method to functionalize SWNTs via combination of covalent and noncovalent approaches for further improving the interfacial strength between SWNTs and CE matrix. A reactive polyimide dispersant, hydroxyl polyimide-graft-bisphenol A diglyceryl acrylate (PIOH-BDA), was synthesized and used to disperse epoxidized SWNTs via noncovalent π−π interaction. The phenolic hydroxyl groups in the backbone of PIOH-BDA react with epoxide groups on SWNTs during thermal curing to achieve covalent functionalization. CE composites with 1 wt% of PIOH-BDA functionalized epoxidized SWNTs show 57%, 71% and 124% increases in Young’s modulus, tensile strength and toughness over neat CE, which are higher than these of CE composites reinforced with pristine SWNTs, epoxidized SWNTs or pristine SWNTs dispersed with PIOH-BDA. These results suggest that the combination of covalent and noncovalent approaches may be the best nanotube functionalization method. Our previous three studies have shown that using a polymeric dispersant that is distinct from the matrix tends to limit the nanotube loading in the composites to low content, which is possibly due to the incompatibility between the dispersant and matrix. In our last study, using a rigid hydroxyl-containing poly(amic acid) (PAA) as both the nanotube dispersant and polyimide matrix precursor, polyimide composite films with multi-walled carbon nanotube (MWNT) content as high as 30 wt% were fabricated by solution casting The MWNT(30 wt%)/PI composites show electrical conductivity of 38.8 S cmwhich is the highest reported value for any conventional solution-processed nanotube composites. They also exhibit Young’s modulus of 9.43 ± 0.14 GPa and tensile strength of 179.2 ± 9.7 MPa, which are higher than other reported values for CNT/PI composites.